Algorithms and Architectures for Parallel Processing : 15th International Conference, ICA3PP 2015, Zhangjiajie, China, November 18-20, 2015, Proceedings, Part I - Wang, Guojun; Zomaya, Albert; Martinez, Gregorio; Li, Kenli; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This four volume set LNCS 9528, 9529, 9530 and 9531 constitutes the refereed proceedings of the 15th International Conference on Algorithms and Architectures for Parallel Processing, ICA3PP 2015, held in Zhangjiajie, China, in November 2015. The 219 revised full papers presented together with 77 workshop papers in these four volumes were carefully reviewed and selected from 807 submissions (602 full papers and 205 workshop papers). The first volume comprises the following topics: parallel and distributed architectures; distributed and network-based computing and internet of things and cyber-physical-social computing. The second volume comprises topics such as big data and its applications and parallel and distributed algorithms. The topics of the third volume are: applications of parallel and distributed computing and service dependability and security in distributed and parallel systems. The covered topics of the fourth volume are: software systems and programming models and performance modeling and evaluation.
Parallel and distributed architectures -- Distributed and network-based computing -- Internet of things and cyber-physical-social computing -- Big data and its applications -- Parallel and distributed algorithms -- Applications of parallel and distributed computing -- Service dependability and security in distributed and parallel systems -- Software systems and programming models -- Performance modeling and evaluation.
Keywords: Computer software; Software engineering; Computer Communication Networks; Database management; Algorithm Analysis and Problem Complexity; Software Engineering; Computer Communication Networks; Database Management